2010
DOI: 10.1149/1.3421974
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Excess Carrier Concentration Control in Fast-Recovery High Power Bipolar Diodes at Low Current Densities

Abstract: The combination of emitter control with local lifetime tailoring by ion irradiation is experimentally analyzed in fast-recovery high power diodes. For this purpose, the carrier lifetime and excess carrier concentration profiles are measured and modeled within the low doped region of unirradiated and helium irradiated diodes under low current densities ͑Ͻ20 A/cm 2 ͒. The interest in working under these current conditions responds to the fact that the only recombination mechanism that modulates the steady-state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Table I shows a lists of the definition of symbols and parameters used for the calculation. The excess carrier distribution (p n ) in the depth direction (x) is expressed using the following equations: 1,25,26)…”
Section: Theoretical and Numerical Analysesmentioning
confidence: 99%
“…Table I shows a lists of the definition of symbols and parameters used for the calculation. The excess carrier distribution (p n ) in the depth direction (x) is expressed using the following equations: 1,25,26)…”
Section: Theoretical and Numerical Analysesmentioning
confidence: 99%
“…These values are higher than those reported earlier [13]. Life time dependence on Voc is exponential in broad terms [14]. It has been found that the carrier life time in the structure of porous heterojunction is always non-uniformly distributed and the difference over large area may be considerable.…”
Section: Measurementmentioning
confidence: 65%
“…The total current density J, the electron current density at the p/i interface J pe , and the hole current density at the i/n interface J nh are related as 27,28)…”
Section: Excess Carrier Density Distributions C I (X)mentioning
confidence: 99%